Increasing the Chances of Natural Conception: Opinion Statement from the the Brazilian Federation of Gynecology and Obstetrics Associations - FEBRASGO Committee of Gynecological Endocrinology - Bruno Ramalho de Carvalho; Ionara Diniz Evangelista Santos Barcelos; Sebastião Freitas de Medeiros; Cristina Laguna Benetti-Pinto; Daniela Angerame Yela; Andrea Prestes Nácul; Gustavo Arantes Rosa Maciel; José Maria Soares Júnior; Ana Carolina Japur de Sá Rosa e Silva; Laura Olinda Bregieiro Fernandes Costa (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Considering that myths and misconceptions regarding natural procreation spread rapidly in the era of easy access to information and to social networks, adequate counseling about natural fertility and spontaneous conception should be encouraged in any kind of health assistance. Despite the fact that there is no strong-powered evidence about any of the aspects related to natural fertility, literature on how to increase the chances of a spontaneous pregnancy is available. In the present article, the Brazilian Federation of Gynecology and Obstetrics Associations (FEBRASGO, in the Portuguese acronym) Committee on Endocrine Gynecology provides suggestions to optimize counseling for non-infertile people attempting spontaneous conception.